2010
DOI: 10.1007/s00125-010-1771-3
|View full text |Cite
|
Sign up to set email alerts
|

DDOST, PRKCSH and LGALS3, which encode AGE-receptors 1, 2 and 3, respectively, are not associated with diabetic nephropathy in type 1 diabetes

Abstract: Aims/hypothesis The AGE receptors 1, 2 and 3, which are encoded by DDOST, PRKCSH and LGALS3, respectively, may be involved in the pathogenesis of diabetic complications. We sought to find out whether these genes are associated with diabetic nephropathy, cardiovascular disease and type 1 diabetes or related quantitative traits. Methods Using the Tagger program, we selected 28 single nucleotide polymorphisms (SNPs) based on the HapMap Centre d'Etude du Polymorphisme (Utah residents with northern and western Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…This contrasts a smaller study in T1D individuals which identified low levels of AGE-R1 mRNA in circulating mononuclear cells in conjunction with elevated levels of serum AGEs, in those individuals with nephropathy [49]. It is worth noting however, that despite not reaching significance, the FinnDiane SNP array identified a trend towards an association between a SNP (rs2170336) in DDOST and DN in individuals with T1D [55]. Therefore, this may be resolved by other longitudinal studies in DN and in the expansion of the sample size in future genetic screens.…”
Section: Age-r1 An Unusal Receptor Involved In Diabetic Nephropathycontrasting
confidence: 60%
See 1 more Smart Citation
“…This contrasts a smaller study in T1D individuals which identified low levels of AGE-R1 mRNA in circulating mononuclear cells in conjunction with elevated levels of serum AGEs, in those individuals with nephropathy [49]. It is worth noting however, that despite not reaching significance, the FinnDiane SNP array identified a trend towards an association between a SNP (rs2170336) in DDOST and DN in individuals with T1D [55]. Therefore, this may be resolved by other longitudinal studies in DN and in the expansion of the sample size in future genetic screens.…”
Section: Age-r1 An Unusal Receptor Involved In Diabetic Nephropathycontrasting
confidence: 60%
“…A SNP array from the FinnDiane population study inferred that there was no association between SNPs of the AGE-R1 gene, DDOST with nephropathy development in individuals with T1D [55]. This contrasts a smaller study in T1D individuals which identified low levels of AGE-R1 mRNA in circulating mononuclear cells in conjunction with elevated levels of serum AGEs, in those individuals with nephropathy [49].…”
Section: Age-r1 An Unusal Receptor Involved In Diabetic Nephropathymentioning
confidence: 90%
“…There exist AGE receptors 1, 2, and 3 (encoded by dolichyl diphospho-oligosaccharide protein glycosyltransferase, protein kinase C substrate 80K-H, and lectin galactoside-binding soluble 3, respectively) (Hoverfelt et al, 2010). RAGE protein is massively up-regulated during diabetes in peripheral nerve and ganglia.…”
Section: Advanced Glycation End-products Inhibitors (Retinopathy mentioning
confidence: 99%
“…This contrasts a smaller study in T1D individuals which identified low levels of AGE-R1 mRNA in circulating mononuclear cells in conjunction with elevated levels of serum AGEs, in those individuals with nephropathy 49 . It is worth noting however, that despite not reaching significance, the FinnDiane SNP array identified a trend towards an association between a SNP (rs2170336) in DDOST and DN in T1D 55 .…”
Section: Age-r1 An Unusual Receptor Involved In Diabetic Nephropathymentioning
confidence: 91%
“…Evidence linking AGE-R1 and diabetic nephropathy in clinical studies is sparse, where the only two studies that investigated this association have contradicting conclusions. A SNP array from the FinnDiane population study inferred that there was no association between SNPs of the AGE-R1 gene, DDOST with nephropathy development in individuals with T1D 55 . This contrasts a smaller study in T1D individuals which identified low levels of AGE-R1 mRNA in circulating mononuclear cells in conjunction with elevated levels of serum AGEs, in those individuals with nephropathy 49 .…”
Section: Age-r1 An Unusual Receptor Involved In Diabetic Nephropathymentioning
confidence: 99%